Berberine attenuates hypoxia‐induced pulmonary arterial hypertension via bone morphogenetic protein and transforming growth factor‐β signaling. Issue 10 (20th February 2019) - Chen, Mingxing; Shen, Hui; Zhu, Linlin; Yang, Hongfeng; Ye, Peng; Liu, Pengfei; Gu, Yue; Chen, Shaoliang
Abstract: Hypoxia‐induced excessive pulmonary artery smooth muscle cell (PASMC) proliferation plays an important role in the pathology of pulmonary arterial hypertension (PAH). Berberine (BBR) is reported as an effective antiproliferative properties applied in clinical. However, the effect of BBR on PAH remains unclear. In the present study, we elucidated the protective effects of BBR against abnormal PASMC proliferation and vascular remodeling in chronic hypoxia‐induced hearts. Furthermore, the potential mechanisms of BBR were investigated. For this purpose, C57/BL6 mice were exposed to chronic hypoxia for 4 weeks to mimic severe PAH. Hemodynamic and pulmonary pathomorphology data showed that chronic hypoxia significantly increased the right ventricular systolic pressure (RVSP), the right ventricle/left ventricle plus septum RV/(LV + S) weight ratio, and the median width of pulmonary arterioles. BBR attenuated the elevations in RVSP and RV/(LV + S) and mitigated pulmonary vascular structure remodeling. BBR also suppressed the hypoxia‐induced increases in the expression of proliferating cell nuclear antigen (PCNA) and of α‐smooth muscle actin. Furthermore, administration of BBR significantly increased the expression of bone morphogenetic protein type II receptor (BMPR‐II) and its downstream molecules P‐smad1/5 and decreased the expression of transforming growth factor‐β (TGF‐β) and its downstream molecules P‐smad2/3. Moreover, peroxisome proliferator‐activated receptor γ expression was significantly decreased in the hypoxia group, and this decrease was reversed by BBR treatment. Our study demonstrated that the protective effect of BBR against hypoxia‐induced PAH in a mouse model may be achieved through altered BMPR‐II and TGF‐β signaling. Abstract : Berberine (BBR) treatment inhibited the elevation of right ventricular systolic pressure (RVSP) and RV/(LV + S) induced by hypoxia. In vivo, the use of BBR increased the expression of bone morphogenetic protein type II receptor (BMPR‐II) and its downstream proteins P‐smad1/5. Moreover, BBR treatment decreased the expression of transforming growth factor‐β (TGF‐β) and its downstream proteins P‐smad2/3. However, both BMPR‐II small interfering RNA (siRNA) and TGF‐β siRNA can abolished the effect. Peroxisome proliferator‐activated receptor γ (PPARγ) expression was significantly decreased in the hypoxia group, and the inhibition effect induced by hypoxia was reversed by treatment with BBR. However, the GW9662, the inhibitor of PPARγ, can abolished the effect.